Pengaruh Perencanaan Pajak, Kepemilikan Manajerial, Ukuran Perusahaan dan Aktiva Pajak Tangguhan Terhadap Praktek Manajemen Laba - Titi Andrayani; Fitriasuri Fitriasuri; M. Titan Terzaghi (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
Earnings management is a condition where earning management intervene in the process of preparing financial statements for the external parties so that it can leveling, raising, and decreasing the profit. This research was aims to find out the effect of tax plan, managerial ownership, company size and deferred tax assets towards the profit management practices. As for the population in this study consisted of 144 manufacture company that registered on Indonesia Stock Exchange with one year of research period in 2016. This research was used purposive sampling. The amount of the company’s sample that fulfill this research’s criteria was 51 companies that meet the criteria of the research variable. The technique analysis that used in this research was multiple linear regression. The examiner’s results shows that the deferred tax assets have positive and significant effects towards the profit management, while the tax plan, managerial ownership and company size have negative and insignificant effects towards the profit management practice.